Evaluation system and exploration optimization for fault-lithologic reservoir on the western slope of Xihu Sag, East China Sea Shelf Basin - Liqing ZHOU; Donghui JIANG; Xinghai ZHOU; Kun LI; Jianjian ZHUANG; Chuang LIU (Shiyou shiyan dizhi, 2022)
With continued progress of exploration degree on the western slope of Xihu Sag of East China Sea Shelf Basin, exploration strategy has gradually changed from structural reservoirs to structural-lithological composite ones. Through the systematic evaluation of the hydrocarbon-generating potential of coal-measure source rocks, it was concluded that coal seams and carbonaceous mudstone are the main source rocks in this area. According to the study of sedimentary system based on the "Source-to-Sink" system, 8 types of structural-lithological composite trap were proposed. Furthermore, the accumulation conditions and distribution characteristics of oil and gas were studied, it is then confirmed that effectiveness of trap is the main controlling factor for oil-and-gas accumulation in the upper and middle members of Pinghu Formation, while the hydrocarbon-supplying capacity and physical properties of reservoir are the main controlling factor in the lower member of Pinghu Formation. Consequently, a comprehensive evaluation system was established. By the means of the comprehensive evaluation of structural-lithological composite reservoirs, the Eocene-Paleocene delta in Yingcuixuan area of the northern segment of the western slope belt, the Eocene tidal flat-delta in Pingnan, Chuyang and Baoshi areas, and the inner zone of Pinghu slope are large-scale reserve areas, which is valuable and favorable for further exploration.